MANAJEMEN KONSTRUKSI BANGUNAN CADANGAN PANGAN BERAS DI KOTA TANJUNG SELOR KABUPATEN BULUNGAN PROVINSI KALIMANTAN UTARA DALAM MEWUJUDKAN EFISIENSI DAN KETAHANAN PANGAN DAERAH - Arman; Sholehah; Enny Harviyanti; Didi Adriansyah (Berajah Journal, 2025)
This research aims to analyze the application of construction management in the development of rice food reserves in Tanjung Selor City to realize project efficiency and support regional food security. The method used was a descriptive qualitative approach, with data collection techniques through interviews with relevant parties, including contractors, project planners, and local government. Data analysis was conducted through data reduction, data presentation, and conclusion drawing to understand the factors that influence the success and constraints in the construction process. The results showed that the implementation of effective construction management contributed to the efficient development of rice food reserves through resource optimization, careful planning, and close supervision in every stage of construction. Constraints encountered include delays in material supply, lack of skilled labor, and time-consuming licensing processes. To improve project effectiveness, strategies that can be implemented include digitizing the licensing system, continuous workforce training, and strengthening coordination between the government, contractors, and building material suppliers. The implementation of these strategies is expected to accelerate project completion, reduce construction costs, and increase the long-term durability of infrastructure, so that rice food reserves can be managed more optimally in supporting regional food security.